This research examines the reactions to the eviction plan of Agus Salim Market by the Pekanbaru City Government - Azim, Zulfadli; Askarial (Sisi Lain Realita, 2024)
This research examines the reactions to the eviction plan of Agus Salim Market by the Pekanbaru City Government, aiming to transform it into a night culinary area similar to Malioboro Market in Yogyakarta. Street vendors (PKL) were given a deadline to dismantle their stalls as they were deemed to violate Building Permit (IMB) regulations and Regional Regulations (Perda) regarding public order. The method employed is a qualitative approach with a descriptive methodology, utilizing victimology theory. The findings indicate that vendors responded to the eviction with physical resistance, such as continuing their sales, and non-physical resistance through demonstrations. The eviction is perceived to have a greater negative impact than benefits, as it is considered to merely transform the Agus Salim area into a replica of Malioboro without considering the needs of the vendors. The preferred solution by the vendors is financial assistance and easily accessible relocation for their businesses.